2009
DOI: 10.1517/17425250902997967
|View full text |Cite
|
Sign up to set email alerts
|

Dietary regulation of P-gp function and expression

Abstract: Food-drug interactions have been associated with clinically important pharmacokinetic and pharmacodynamic changes of a drug. The aim of this paper is to review the regulation of P-glycoprotein (P-gp) by dietary components and to correlate the changes in cellular P-gp function and expression with drug bioavailability. In summary, the published literature has provided extensive data supporting the modulation of drug bioavailability through P-gp regulation by components in food groups such as fruit juices, spices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 142 publications
1
31
0
5
Order By: Relevance
“…It has become an established fact now that p-gp mediates MDR by actively transporting a wide range of anticancer drugs including paclitaxel, doxorubicin, daunorubicin, vinca alkaloids and eteposide (Zhang et al, 2003;Yoshida et al, 2005;Ferreira et al, 2006;Nabekura, 2010a;Yang et al, 2014). P-gp can interact and bind with a large number of structurally and functionally unrelated agents which suggests its multiple binding sites (Zhang et al, 2009;Chen et al, 2012). According to the interactions, these agents can be classified into three main groups: substrate, inhibitors, and modulators.…”
Section: Enhancing Activity Of Anticancer Drugs In Multidrug Resistanmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become an established fact now that p-gp mediates MDR by actively transporting a wide range of anticancer drugs including paclitaxel, doxorubicin, daunorubicin, vinca alkaloids and eteposide (Zhang et al, 2003;Yoshida et al, 2005;Ferreira et al, 2006;Nabekura, 2010a;Yang et al, 2014). P-gp can interact and bind with a large number of structurally and functionally unrelated agents which suggests its multiple binding sites (Zhang et al, 2009;Chen et al, 2012). According to the interactions, these agents can be classified into three main groups: substrate, inhibitors, and modulators.…”
Section: Enhancing Activity Of Anticancer Drugs In Multidrug Resistanmentioning
confidence: 99%
“…Piperine has been reported to enhance the activity of anticancer drug in various drug resistant cancer cells (Bezerra et al, 2008). Other studies have shown that piperine inhibits the efflux activity of p-gp and alters the clinical pharmacokinetic profile of several drugs which are p-gp substrate (Zhang et al, 2009). However, only one recent study by Li et al (2011) has provided evidence that piperine sensitizes multidrug resistant tumors cells to chemotherapy through ABC transporter inhibition.…”
Section: Piperinementioning
confidence: 99%
“…C max and AUC values were lower in subjects homozygous for the MDR1 3435T variant compared with subjects with the 3435C/T and 3435C/C genotypes . Other than genetic polymorphism, many factors have been found to alter P-gp expression including but not limited to food intake (Deferme et al, 2002;Zhang et al, 2009), diseases (Liu et al, 2008;Dopp et al, 2009), and drugs (Fiegenbaum et al, 2005) .…”
Section: )mentioning
confidence: 99%
“…Unfortunately, this is not feasible in real life situation where real patients are being recruited, and most of them get discharged after much less than 24 h post stenting. It should be noted that several other studies terminated sampling by 8 h or even less (Deferme et al, 2002;Zhang et al, 2009).…”
Section: )mentioning
confidence: 99%
“…However in situations where MRP2 may be deficient, MRP3 may be upregulated, apparently to compensate for the diminished ability to excrete organic acids into bile (Keitel et al, 2000). Chronic administration of PCs however, may result in the upregulation of transporters via activation of the pregnane X receptor (PXR) or the aryl hydrocarbon receptor (AhR) in hepatocytes, lessening the effects of inhibition (Lim & Lim, 2006;Zhang et al, 2009). …”
Section: Excretionmentioning
confidence: 99%